Long Non-coding Wilms Tumor 1 Antisense RNA in the Development and Progression of Malignant Tumors - Zhang, Ye; Fan, Lin-Jun; Zhang, Yi; Jiang, Jun; Qi, Xiao-Wei (Frontiers in Oncology, 2020)
A growing number of studies have shown that long non-coding RNAs (lncRNAs) play an important role in tumor development and progression and are key molecules affecting tumor progression. The lncRNA WT1-AS (Wilms tumor 1 antisense RNA) is specifically expressed in various malignant tumors. In particular, WT1-AS expression is upregulated in colon cancer and breast cancer, but is significantly downregulated in cervical cancer, liver cancer, and kidney cancer. The level of WT1-AS expression is closely related to the size, stage, and patient survival rate of these cancers. In this article, we review the modes of action, expression, function, and mechanisms of WT1-AS in different tumors to provide new targets for tumor diagnosis and treatment.